Anharmonic correlated Debye model high-order expanded Debye-Waller factors of bcc crystals. Application to metallic Wolfram - Hung, Nguyen Van; Hue, Trinh Thi; Trung, Nguyen Bao; Toan, Nguyen Cong (VNU Journal of Science: Mathematics - Physics; Vol 33 No 1, 2017)
Abstract : Anharmonic correlated Debye model is derived for Debye-Waller factors of bcc (body-centered cubic) crystals presented in terms of cumulant expansion up to the fourth order. The many-body effects are taken into account in the present one-dimensional model based on the anharmonic effective potential that includes interactions of absorber and backscatterer atoms with their first shell near neighbors, where Morse potential is assumed to describe the single-pair atomic interaction. Analytical expressions for dispersion relation, correlated Debye frequency and temperature and four first temperature-dependent XAFS (X-ray absorption fine structure) cumulants of bcc crystals have been derived using the many-body perturbation approach. Numerical results for W are found to be in good agreement with experiment.  Keywords: Debye-Waller factor, effective potential, correlated Debye model, bcc crystals.